2008
DOI: 10.1152/ajprenal.00003.2008
|View full text |Cite
|
Sign up to set email alerts
|

Increased inorganic phosphate induces human endothelial cell apoptosis in vitro

Abstract: Chronic kidney disease with hyperphosphatemia is associated with accelerated atherosclerosis and endothelial dysfunction. However, the contribution of high serum phosphate levels to endothelial injury is incompletely understood. The aim of this work was to evaluate the responses of endothelial cells to elevated levels of extracellular phosphate in vitro. High phosphate in concentrations similar to those observed in uremia-associated hyperphosphatemia (>2.5 mM) induced apoptosis in two endothelial cell lines (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(159 citation statements)
references
References 33 publications
9
148
0
2
Order By: Relevance
“…Other studies, including our investigation, demonstrated that elevation of extracellular phosphate levels could induce endothelial dysfunction by an increase in oxidative stress and apoptosis, and a decrease in eNOS activity 48,49) . Inhibition of phosphate transport activity by phosphonoformic acid or siRNA can inhibit both calcification in vascular smooth muscle cells 44,50) and oxidative stress in endothelial cells 48,49) . Therefore, the phosphate transport activity of type III sodium-dependent phosphate transporters is important in the development of vascular complications leading to arteriosclerosis.…”
Section: Cardiovascular Disease and Transporterssupporting
confidence: 55%
“…Other studies, including our investigation, demonstrated that elevation of extracellular phosphate levels could induce endothelial dysfunction by an increase in oxidative stress and apoptosis, and a decrease in eNOS activity 48,49) . Inhibition of phosphate transport activity by phosphonoformic acid or siRNA can inhibit both calcification in vascular smooth muscle cells 44,50) and oxidative stress in endothelial cells 48,49) . Therefore, the phosphate transport activity of type III sodium-dependent phosphate transporters is important in the development of vascular complications leading to arteriosclerosis.…”
Section: Cardiovascular Disease and Transporterssupporting
confidence: 55%
“…PO 4 and Ca × PO 4 were evaluated at the beginning of the study, after 1 and 2 weeks of chewing gum use and after 2 and 4 weeks from the chewing gum use withdrawal. 8 hsCRP was measured from the available blood samples corresponding to the beginning of the study, after 2 weeks of chewing gum use, and after 4 weeks from the chewing gum use withdrawal, and analyzed with corresponding PO 4 and Ca × PO 4 values.…”
Section: Methodsmentioning
confidence: 99%
“…Serum PO 4 and calcium levels were determined by a spectrophotometric assay using a flex reagent cartridge (Dade Behring, Newark, NJ, USA) and hsCRP by immunonephelometry (Dade Behring).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Além disso, o Pi pode induzir a apoptose de células endoteliais através do aumento do estresse oxidativo. 42 Uma das maiores dificuldades em interpretar os efeitos deletérios do Pi in vivo é determinar se eles são resultado de sua ação direta ou de mecanismos indiretos, por exemplo, via aumento de FGF-23 e PTH. Através de estudos em modelo animal (ratos) de DRC, nos quais os animais foram submetidos a paratireoidectomia e, posteriormente, à infusão contínua controlada de PTH, Neves e cols.…”
Section: Mecanismos De Lesão Cardiovascular Pelo Fosfato -Lições De Eunclassified